Pathophysiologic mechanisms of cerebral endotheliopathy and stroke due to Sars-CoV-2. Issue 6 (June 2021) - Kakarla, Visesha; Kaneko, Naoki; Nour, May; Khatibi, Kasra; Elahi, Fanny; Liebeskind, David S; Hinman, Jason D
Cerebrovascular events have emerged as a central feature of the clinical syndrome associated with Sars-CoV-2 infection. This increase in infection-related strokes is marked by atypical presentations including stroke in younger patients and a high rate of hemorrhagic transformation after ischemia. A variety of pathogenic mechanisms may underlie this connection. Efforts to identify synergism in the pathophysiology underlying stroke and Sars-CoV-2 infection can inform the understanding of both conditions in novel ways. In this review, the molecular cascades connected to Sars-CoV-2 infection are placed in the context of the cerebral vasculature and in relationship to pathways known to be associated with stroke. Cytokine-mediated promotion of systemic hypercoagulability is suggested while direct Sars-CoV-2 infection of cerebral endothelial cells may also contribute. Endotheliopathy resulting from direct Sars-CoV-2 infection of the cerebral vasculature can modulate ACE2/AT1 R/MasR signaling pathways, trigger direct viral activation of the complement cascade, and activate feed-forward cytokine cascades that impact the blood-brain barrier. All of these pathways are already implicated as independent mechanisms driving stroke and cerebrovascular injury irrespective of Sars-CoV-2. Recognizing the overlap of molecular pathways triggered by Sars-CoV-2 infection with those implicated in the pathogenesis of stroke provides an opportunity to identify future therapeutics targeting both Sars-CoV-2 and stroke thereby reducing the impact of the global pandemic.